2019
DOI: 10.1007/s00222-019-00907-z
|View full text |Cite
|
Sign up to set email alerts
|

Motivic spheres and the image of the Suslin–Hurewicz map

Abstract: We show that an old conjecture of A.A. Suslin characterizing the image of a Hurewicz map from Quillen K-theory in degree n to Milnor K-theory in degree n admits an interpretation in terms of unstable A 1 -homotopy sheaves of the general linear group. Using this identification, we establish Suslin's conjecture in degree 5 for infinite fields having characteristic unequal to 2 or 3. We do this by linking the relevant unstable A 1 -homotopy sheaf of the general linear group to the stable A 1 -homotopy of motivic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Furthermore, the map on the right fails to be surjective. The unstable description above is not present in the literature, but it is equivalent to the results stated in [AFW20]. In [RSØ19], the stable motivic 1-stem was computed in the terms above: the above sequence is exact on the left stably.…”
Section: The Motivic J-homomorphismmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the map on the right fails to be surjective. The unstable description above is not present in the literature, but it is equivalent to the results stated in [AFW20]. In [RSØ19], the stable motivic 1-stem was computed in the terms above: the above sequence is exact on the left stably.…”
Section: The Motivic J-homomorphismmentioning
confidence: 95%
“…Indeed, in joint work with T.B. Williams [AFW20] we showed that S n can described using a "Hurewicz map" analyzed by Andrei Suslin [Sus84]. Suslin's conjecture on the image of this map is equivalent to the following conjecture.…”
Section: Moreover If K Admits a Complex Embedding Then The Map πmentioning
confidence: 99%
See 1 more Smart Citation
“…This closes the gap between three and five in the set of degrees for which Suslin's conjecture was previously known. See the introduction of [3] for more details on its history, as well as Suslin's original paper [25].…”
Section: Theorem Let F Be An Infinite Field Of Characteristic Differe...mentioning
confidence: 99%
“…Along the way, the homotopy modules π 1 P 2 and π 2 P 2 will be determined, based on computations in [23] and [22]. These computations provide an ingredient to complete the program Aravind Asok, Jean Fasel and Ben Williams developed in [3] to prove Suslin's conjecture on the Suslin-Hurewicz homomorphism from Quillen to Milnor K -theory in degree four.…”
Section: Introductionmentioning
confidence: 99%